The Needs of Science Major Students at Madrasah Aliyah Al-Bairuni Jombang for Instagram Content-Based Nahwu Materials - Lailil Maulidiyah; Siti Sulaikho (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2024)
Nahwu material tends to be difficult, making students feel bored quickly and less interested in learning it more deeply. The thing that needs to be considered is variation in learning. One of the variations in learning is using social media based on Instagram content so that students can understand and make the learning atmosphere interesting. This study aims to uncover the requirements of students with regard to Instagram content focused on nahwu. Furthermore, the intention is to demonstrate that Instagram, typically utilized for sharing photos and videos, is also possibly utilized effectively as a learning tool. The study utilized a descriptive qualitative research approach as its research method. Observation interviews served as the approach for collecting data, including up to 5 individuals who met the criteria of being class XII students and had studied nahwu material. The Miles and Huberman model is utilized in the method for analyzing data, which involves Data collection, data simplification, data display, and drawing/verifying final thoughts. The findings of this research show that students need to have a sense of urgency in Instagramming content related to Nahwu studies. The reason for displaying nahwu content on Instagram is to make the learning process more engaging and easier to comprehend. Hence, the media must communicate nahwu material.